Effect of sperm agglutinating antibodies on in vitro fertilization in hamster - Bathla, H; Sangha, G K; Guraya, S S (The Indian Journal of Animal Sciences, 2012)
The effect of monospecific antisera on in vitro fertilization of hamster oviductal oocytes, primed with PMSG/hCG and incubated under liquid paraffin in m-TALP at 37Â°C, was studied. The monospecific antisera obtained after titration with various tissues showed sperm agglutinating activity. Per cent binding and penetration by capacitated spermatozoa to egg zona pellucida decreased significantly in the presence of monospecific antisera compared to the control. Thus sperm, agglutinating antibodies interfere with crucial events, viz. sperm binding and penetration which are important before fertilization.